Student problem solving skills in PBL model: Viewed from the discourse sheet - Nurkhairo Hidayati; Tengku Idris; Peny Husna Handayani (Biosfer: Jurnal Pendidikan Biologi, 2022)
Problem solving ability relates to a person's ability to manage and find appropriate solutions in unexpected and complex conditions. Problem solving skills are not something that is innate, but these skills can be developed when a person is given the opportunity to solve problems. This ability is very important for students, especially when they enter the world of work. This study aims to determine the problem-solving ability of students when completing the problem discourse sheet in the PBL model. The type of research used is descriptive quantitative using a sample of 37 students who take the Human Physiology Anatomy course in the biology education study program at the Islamic University of Riau. The research instrument is in the form of problem discourse and scoring rubric. Problem solving indicators consist of identifying terms, formulating questions, considering, and finding solutions from problem formulations and making and determining conclusions. The data obtained were analyzed by scoring each answer given by students. The results showed that students' problem-solving abilities differed on each indicator. The indicator that occupies the highest score is formulating questions and the lowest is making and determining conclusions. Based on the results of the study, it can be concluded that the problem-solving ability of students while completing the problem discourse sheet in the PBL model is in the very good category.